A STUDY ON THE SYNTHESIS OF MgAl2O4 SPINEL BY STARCH ASSISTED SOL-GEL PROCESS - Tuyen, Tran Ngoc; Quyen, Nguyen Duc Vu; Ngoc, Tran Minh; Tin, Dang Xuan; Hai, Ho Van Minh (Vietnam Journal of Science and Technology, 2015)
In this paper, the synthesis of ceramic spinel MgAl2O4 by starch assisted sol - gel process is presented. The gel mixture was prepared by using Mg(NO3)2.6H2O, Al(NO3)3.9H2O as precursors and starch as a gel agent. The study focused on relevant components of gel mixture and the calcinating temperature. The results showed that suitable molar proportion of Mg2+/Al3+; starch/(Mg2+ + Al3+) and H2O/starch were 0.5, 0.4 and 60, respectively. The calcination at 1100 oC for 60 minutes was suitable for forming phase of spinel. The product was a single phase of spinel MgAl2O4 with excellent crystallinity and uniform size in the range of 300 to 400 nm.